Continuous integrated filtration, washing and drying of aspirin: digital design of a novel intensified unit. Issue 3 (2021) - Destro, Francesco; Wang, Vivian; Abdi, Mesfin; Feng, Xin; Wood, Erin; Coleman, Simon; Firth, Paul; Barton, Alastair; Barolo, Massimiliano; K. Nagy, Zoltan
Abstract: Within the recent modernization of pharmaceutical manufacturing, an important milestone consists in developing enabling technologies for end-to-end continuous production of drug products. Continuous filtration, washing and drying of active pharmaceutical ingredients from mother liquors in upstream manufacturing are critical steps for achieving end-to-end continuous production. In this work, we develop a mathematical model for a novel intensified carousel system capable of continuously filtering, washing and drying a slurry stream into a dry crystals cake. The mathematical model consists of detailed dynamic differential mass, energy and momentum balances, capable of tracking the solvents and impurities content in the cake (critical quality attributes) across the entire carousel. We successfully demonstrate the model features by identifying the probabilistic design space in a simulation study for the isolation of aspirin crystals in the carousel, accounting for model uncertainty through Monte Carlo simulations.